Bacterial phyla: microbiota of kingdom animalia - Dinesh Nalage; Rahul Kale; Tejswini Sontakke; Vidya Pradhan; Ashwini Biradar; Jayan Duminda Mahesh Senevirathna; Reshma Jaweria; Tara Dighe; Prashant Dixit; Rohit Patil; P. S. Kudnar (Academia Biology)
The gut microbiome is a vital factor in animal health and development, influenced by various elements. This review explores the bacterial strains within the microbiome and their roles in digestion, immunity, disease causation, and overall host well-being. Across all mammals, Bacteroidetes and Firmicutes are the dominant phyla, with omnivores and carnivores also harboring Proteobacteria. In canids, Firmicutes, Bacteroidetes, Proteobacteria, and Fusobacteriota are the predominant phyla. Bacteroidetes exhibit remarkable prowess in digesting organic material, while Proteobacteria are essential for oxygen uptake in anaerobic environments. Firmicutes, known for their health-promoting properties, can counteract the effects of harmful bacteria, such as Clostridium difficile. Notably, the host’s diet exerts a significant influence on microbiome composition, as evidenced by the division of gut microbiomes into two distinct groups: herbivores in one and carnivores/omnivores in the other. These findings lay a vital foundation for future endeavors in animal health and conservation. As the field progresses, we anticipate uncovering even more profound insights into the intricate relationship between the gut microbiome and human health.